Die moederskoot van Israel: "n Teologiese besinning oor die nuwe navorsingsresultate met betrekking tot die totstandkoming van Israel - Bezuidenhout, L. C. (Hervormde teologiese studies, 1996)
The womb of Israel: Tbeological reflections on recent research results concerning the origin of Israel. Recent research concerning the origin of Israel has the potential to cause theological disorientation. The birth of Israel and its religion was unpretentious and not as unique as it may appear in the Biblical accounts. It is necessary to analyse and evaluate these results and to integrate it into a theological perspective. These results can induce theological benefits if it is perceived in the right perspective.